Physiological concentrations of unconjugated bilirubin prevent oxidative stress-induced hepatocanalicular dysfunction and cholestasis - Basiglio, Cecilia Lorena (2014)
Fil: Fil: Basiglio, Cecilia Lorena. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Fisiología Experimental (IFISE-CONICET); Argentina.